Lower limbs lengthening over the intramedullary nail versus lengthening by Ilizarov technique - E. A. Shchepkina; I. V. Lebedkov; L. N. Solomin; K. L. Korchagin; F. K. Sabirov; D. G. Parfeev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Lengthening over the nail (LON) combines the advantages of external and internal fixations.The objective was to compare the effectiveness of the application, to assess the structure and frequency of complications in patients treated with lengthening by Ilizarov technique and lengthening over the nail.Methods and materials. We analyzed 55 LON cases and 64 cases lengthening by Ilizarov technique. The duration of the external fixation period, complications and quality of the patient life were compared.Results. The external fixation period in LON group was 4 times less than in the Ilizarov technique group. There were 25 complications (45.5 %) in LON group and 54 complications (84.4 %) in the Ilizarov technique group. Femur lengthening was associated with a greater number of complications in both groups. Pin infections were 2.5 times less frequently in the femur LON group. Knee contractures were only in Ilizarov technique group (11.4 %). Ankle joint contracture was noted with the same frequency during tibial lengthening in both groups. Disorders of the consolidation were 2 times more often in the femur LON group and 5 times more often in the tibial lengthening with Ilizarov technique. Premature fusion was observed only in the LON group. There were 2 times less fractures of the half-pins and wires in the LON group.Conclusions. A reduction of external fixation period in LON group correlates with the 2-fold decrease of complications and an increase of the treatment comfort. LON is promising for wider clinical applications.